Systematics of the South American species of Cylindrostethus Mayr, 1865 (Hemiptera:Heteroptera:Gerridae), with a new species from Amazonian Brazil and Peru - Floriano, Carla Fernanda Burguez [UNESP]; Paladini, Andressa; Cavichioli, Rodney Ramiro (CSIRO Publishing, 2016)
Water striders (pond skaters) occur worldwide and are conspicuous in most aquatic environments, but the taxonomy of many groups remains unresolved. Here we revise the South American species of the Palaeo- and Neotropically distributed Cylindrostethus Mayr, 1865, a genus characterised by its long, cylindrical body and fast jumping-gliding locomotion. Using a cladistic analysis of morphological characters, we confirm the subdivision of Neotropical Cylindrostethus into two major groups. Nine species of Cylindrostethus are recognised from South America, one of which was recently discovered in Amazonian Brazil and Peru: C. bassleri Drake, 1952; C. bilobatus Kuitert, 1942; C. drakei, sp. Nov.; C. hungerfordi Drake & Harris, 1934; C. linearis (Erichson, 1848); C. meloi Floriano & Cavichioli, 2013; C. palmaris Drake & Harris, 1934; C. podargus Drake, 1958; C. regulus (White, 1879). Two species are placed in synonymy: (C. podargus≤C. stygius Drake, 1961, syn. Nov.); (C. linearis≤C. erythropus (Herrich-Schäffer, 1850), syn. Nov.). A key to the nine species is provided, along with detailed descriptions and illustrations. Journal compilation.
Keywords: Cylindrostethinae; Neotropical; taxonomy; water striders